2019
DOI: 10.18772/22019032750
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Research Methods in the Social Sciences

Abstract: for their generous contributions towards the publication of this book.We are also greatly indebted to the following people who selflessly agreed to review a chapter, purely as an exercise in academic citizenship and as a contribution to a high standard of academic knowledge:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 411 publications
0
3
0
Order By: Relevance
“…Additionally, the immediate testing following the VR intervention may amplify the observed benefits, a phenomenon known as the "intervention-testing effect", suggesting that recent exposure to an educational intervention could enhance the performance on subsequent assessments irrespective of the medium used [67]. Comparative analysis with non-VR interventions, such as educational videos, could further clarify VR's unique advantages.…”
Section: Limitations and Recommendations For Future Researchmentioning
confidence: 99%
“…Additionally, the immediate testing following the VR intervention may amplify the observed benefits, a phenomenon known as the "intervention-testing effect", suggesting that recent exposure to an educational intervention could enhance the performance on subsequent assessments irrespective of the medium used [67]. Comparative analysis with non-VR interventions, such as educational videos, could further clarify VR's unique advantages.…”
Section: Limitations and Recommendations For Future Researchmentioning
confidence: 99%
“…Literature has indicated that research methods play an important role in the quality of research as well as educating young researchers; however, the application thereof is unclear, which can be harmful to the field of psychology (Scholtz, De Klerk, & De Beer, 2020). The recently published research methodology book by Laher, Fynn and Kramer (2019) was, according to the authors, written in response:…”
mentioning
confidence: 99%
“…(Kramer, Fynn, & Laher, 2019, p. 1) In the light of this statement, as well as the article written by Scholtz et al (2020), we as reviewers had to ask ourselves, did Laher et al (2019) achieve what they set out to do? Laher et al (2019) mention that the field of social science is ever growing and expanding. Therefore, it can become quite challenging in keeping up with the newest research methods and development thereof.…”
mentioning
confidence: 99%